The Subaltern's Failure of Recognition in Shakespeare's The Merchant of Venice (1599): Postcolonial Psychoanalysis Study - Pandu, Indiwara (NOBEL: Journal of Literature and Language Teaching, 2020)
This study seeks to find the struggle of self-recognition from the subaltern group by using the postcolonial psychoanalysis perspective. Shylock and Prince Morocco, considered to be inferior, are dealing with the recognition to make themselves as superior as the dominant class. From the analysis, supported by Fanon’s Black Skin White Mask (1952), recognition is one of the ways for the Other to enter western society. In doing this study, close reading is applied to analyze the following discussion: (1) the racial issue portrayed in The Merchant of Venice; 2) the struggle of the marginalized to gain the recognition; 3) The failure of recognition. Throughout the analysis, both Shylock and Prince Morocco fail to obtain recognition as a way to cross in western society. The constructed society based on western domination does not enable the subaltern to gain their recognition.